Nuclease‐resistant 63‐bp trimeric siRNAs simultaneously silence three different genes in tumor cells. Issue 1 (29th December 2017) - Gvozdeva, Olga V.; Gladkih, Daniil V.; Chernikov, Ivan V.; Meschaninova, Mariya I.; Venyaminova, Alya G.; Zenkova, Marina A.; Vlassov, Valentin V.; Chernolovskaya, Elena L.
Abstract : We designed a multimeric nuclease‐resistant 63‐bp trimeric small‐interfering RNA (tsiRNA) comprising in one duplex the sequence of siRNAs targeting mRNAs of MDR1, LMP2, and LMP7 genes. We show that such tsiRNA is able to suppress the expression of all the target genes independently and with high efficiency, acting via a Dicer‐dependent mechanism. tsiRNA is diced into 42‐ and 21‐bp duplexes inside the cell. tsiRNA‐induced gene silencing is characterized by kinetics similar to that of canonical siRNA, while the silencing efficiency is significantly higher than that of canonical siRNA with the same sequence. Abstract :